Nonlinear Optics Nonlinear Nanophotonics and Novel Materials for Nonlinear Optics - Lembrikov, Boris I. (IntechOpen, 2022)
This book examines nonlinear optical effects in nonlinear nanophotonics, plasmonics, and novel materials for nonlinear optics. It discusses different types of plasmonic excitations such as volume plasmons, localized surface plasmons, and surface plasmon polaritons. It also examines the specific features of nonlinear optical phenomena in plasmonic nanostructures and metamaterials. Chapters cover such topics as applications of nanophotonics, novel materials for nonlinear optics based on nanoparticles, polymers, and photonic glasses.